Determination of Quercetin in Medicinal Plants Such as Rose Hip (Rosa canina), Bettle (Urtica dioica), Terebinth (Terebinthina chica) and Purslane (Portulace oleracea) using HPLC-MS Method - Ozcan, Cemile; Dilgin, Yusuf; Yaman, Mehmet (Asian Journal of Chemistry, 2012)
A simple and rapid high performance liquid chromatography-mass spectrometry (HPLC-MS) method was developed for the determination of quercetin in four plants and fruits samples which are rose hip (Rosa canina), nettle (Urtica dioica), terebinth (Terebinthina chica) and purslane (Portulace oleracea). For this purpose, flow rate of mobile phase, fragmentor potential, injection volume and column temperature were optimized as 0.6 mL min(-1), 140 V, 5 mu L and 30 degrees C, respectively. While the average recoveries were found at least 90 %, limit of detection and limit of quantification were found to be 0.1 and 0.4 mg L-1, respectively. The relative standard deviation for retention time and peak area of 25 mg L-1 quercetin was found to be 2.4 % and 3.5 %, respectively. The optimized method was successfully applied determination of quercetin in the plant and fruits samples after their extraction with a mixture of HCl, methanol and ascorbic acid.
Keywords: HPLC-MS; Quercetin; Rose hip; Nettle; Purslane; Terebinth; Flavonoids